The Kada Tominaa in Toraja Rituals Using Metaphorical Expression Analysis - Anastasia Baan; Markus Deli Girik Allo; Andi Anto Patak; Cris T. Zita; Andi Asrifan (NAJAHA, 2025)
Kada Tominaa (Ethics Advice) is a distinctive form of Toraja oral literature expressed in ritual contexts, especially in Rambu Solo’ (funeral) and Rambu Tuka' (thanksgiving). It serves as both ritual poetry and a cultural medium that conveys ethical teachings, cosmological beliefs, and communal values across generations. This research employed a qualitative descriptive approach to analyse the literary expressions of Kada Tominaa. Data were collected from ritual speeches delivered by traditional speakers (Tominaa) and supported by interpretations from community elders. The analysis focused on specialised vocabulary, metaphorical meanings, and sociocultural functions embedded in ritual discourse. The study reveals that Kada Tominaa employs specialised vocabulary rarely used in daily Toraja conversation, including Ombo’ (born), Kombong Mentolino (becoming human), Tangkean Suru’ (family prayers), and Tibaen Passoeanna (let him go there). These terms carry layered metaphorical meanings, symbolising the interconnectedness of life and death, human responsibility, communal solidarity, gratitude, leadership, and spiritual continuity. The vocabulary serves as a cultural repository, preserving ancestral wisdom while reinforcing Torajan identity and social cohesion. The findings highlight that Kada Tominaa is more than ceremonial speech; it is a vital medium of cultural continuity that integrates language, metaphor, and ritual performance. By embodying ethical principles and cosmological perspectives, Kada Tominaa sustains the Toraja worldview and ensures the transmission of traditions across generations.